A Standardized Needs Assessment Tool to Inform the Curriculum Development Process for Pediatric Resuscitation Simulation-Based Education in Resource-Limited Settings - Shilkofski, Nicole; Crichlow, Amanda; Rice, Julie; Cope, Leslie; Kyaw, Ye Myint; Mon, Thazin; Kiguli, Sarah; Jung, Julianna (Frontiers in Pediatrics, 2018)
Introduction: Under five mortality rates (UFMR) remain high for children in low and middle-income countries (LMICs) in the developing world. Education for practitioners in these environments is a key factor to improve outcomes that will address United Nations Sustainable Development Goals 3 and 10 (good health and well being and reduced inequalities). In order to appropriately contextualize a curriculum using simulation, it is necessary to first conduct a needs assessment of the target learner population. The World Health Organization (WHO) has published a tool to assess capacity for emergency and surgical care in LMICs that is adaptable to this goal. Materials and Methods: The WHO Tool for Situational Analysis to Assess Emergency and Essential Surgical Care was modified to assess pediatric resuscitation capacity in clinical settings in two LMICs: Uganda and Myanmar. Modifications included assessment of self-identified learning needs, current practices, and perceived epidemiology of disease burden in each clinical setting, in addition to assessment of pediatric resuscitation capacity in regard to infrastructure, procedures, equipment and supplies. The modified tool was administered to 94 respondents from the two settings who were target learners of a proposed simulation-based curriculum in pediatric and neonatal resuscitation. Results: Infectious diseases (respiratory illnesses and diarrheal disease) were cited as the most common causes of pediatric deaths in both countries. Self-identified learning needs included knowledge and skill development in pediatric airway/breathing topics, as well as general resuscitation topics such as CPR and fluid resuscitation in shock. Equipment and supply availability varied substantially between settings, and critical shortages were identified in each setting. Current practices and procedures were often limited by equipment availability or infrastructural considerations. Discussion and Conclusions: Epidemiology of disease burden reported by respondents was relatively consistent with WHO country-specific UFMR statistics in each setting. Results of the needs assessment survey were subsequently used to refine goals and objectives for the simulation curriculum, and to ensure delivery of pragmatic educational content with recommendations that were contextualized for local capacity and resource availability. Effective use of the tool in two different settings increases its potential generalizability.